Development of a bladder instillation of the indoloquinone anticancer agent EO-9 using tert-butyl alcohol as lyophilization vehicle - van der Schoot, Sabien C. (Springer-Verlag, 2007)
The purpose of this research was to develop a stable bladder instillation of EO-9 for the treatment of superficial bladder cancer. First, stability and dissolution studies were performed. Subsequently, the freeze-drying process was optimized by determination of the freeze-drying characteristics of the selected cosolvent/water system and differential scanning calorimetry analysis of the formulation solution. Furthermore, the influence of the freeze-drying process on crystallinity and morphology of the freeze-dried product was determined with x-ray diffraction analysis and scanning electron microscopy, respectively. Subsequently, a reconstitution solution was developed. This study revealed that tert-butyl alcohol (TBA) can be used to both dramatically improve the solubility and stability of EO-9 and to shorten the freeze-drying cycle by increasing the sublimation rate. During freeze drying, 3 TBA crystals were found: TBA hydrate-ice crystals, crystals of TBA hydrate, and a third crystal, probably composed of TBA hydrate crystals containing ≈90% to 95% TBA. Furthermore, it was shown that crystallization of TBA hydrate was inhibited in the presence of both sodium bicarbonate (NaHCO(3)) and mannitol. Addition of an annealing step resulted in a minor increase in the crystallinity of the freeze-dried product and formation of the δ-polymorph of mannitol. A stable bladder instillation was obtained after reconstitution of the freeze-dried product (containing 8 mg of EO-9, 20 mg of NaHCO(3), and 50 mg of mannitol per vial) to 20 mL with a reconstitution solution composed of propylene glycol/water for injection (WfI)/NaHCO(3)/sodium edetate 60%/40%/2%/0.02% vol/vol/wt/wt, followed by dilution with Wfl to a final volume of 40 mL.